Rancang Bangun Sistem Monitoring Radiasi Sinar-X Berbasis Internet of Things (IoT) - Muttaqin, Rodhotul; Prayitno, Wasi Sakti Wiwit; Setyaningsih, Natalia Erna; Nurbaiti, Upik (Jurnal Pengelolaan Laboratorium Pendidikan, 2026)
Excessive exposure to X-ray radiation can be harmful to human health; therefore, it is important to regularly monitor its intensity, especially in laboratories equipped with ionizing radiation facilities. This research aims to develop an X-ray radiation monitoring system designed to measure radiation levels in the Material Characterization Unit of the Physics Laboratory at Universitas Negeri Semarang. The research method refers to the prototype model, which consists of several stages: communication, quick planning, quick design modeling, and prototype construction. This monitoring system is essential due to the presence of an X-Ray Diffractometer (XRD) machine, which serves as a source of ionizing radiation.The developed system consists of an X-ray radiation detector integrated with an ESP32 microcontroller that transmits data to a cloud server via a Wi-Fi protocol. The radiation detector used in this monitoring system is a Geiger-Müller counter. The measured radiation data can also be displayed on an OLED 128x64 screen. Data acquisition is recorded online using the Google Sheets Application Programming Interface (API), enabling real-time data logging. Experimental results of radiation measurements inside the XRD unit show a radiation dose of 319.2 µSv at a distance of 30 cm from the tube at an angle of 30°, while environmental radiation measurements indicate a dose of 0.815 µSv. The monitoring system’s measurements were compared with those obtained from a standard survey meter, Ludlum Model 3. The results demonstrate that the developed system is capable of measuring X-ray radiation in real-time and can be effectively used for X-ray radiation monitoring.